(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Jaundice is the yellow color of skin and mucous membranes due to accumulation of bile pigments in blood and their deposition in body tissues. Jaundice should be distinguished from cholestasis, which refers to a decreased rate of bile flow. Depending on the clinical situation, jaundice and cholestasis may coexist or each may exist without the other. Although many sources confidently say that jaundice can be recognized when the serum bilirubin rises to 2 to 2.5 mg/dl, experienced clinicians often cannot see a yellow skin coloration until the serum bilirubin is at least 7 to 8 mg/dl.